Harnessing a p‐Quinone Methide Intermediate in the Biomimetic Total Synthesis of the Highly Active Antibiotic 20‐Deoxy‐Elansolid B1. Issue 22 (5th April 2017) - Wang, Liang Liang; Candito, David; Dräger, Gerald; Herrmann, Jennifer; Müller, Rolf; Kirschning, Andreas
Abstract: The polyketide, 20‐deoxy elansolid B1, was prepared by a convergent strategy that relied on a putative biomimetic intramolecular Diels–Alder cycloaddition (IMDA) via a vinylic p ‐quinone methide intermediate to furnish the key tetrahydroindane unit. The ( Z, E, Z )‐configured triene unit was constructed by Pd‐catalyzed Suzuki–Miyaura and Stille cross‐coupling reactions without isomerization of any of the olefinic double bonds. Formation of a p ‐methide quinone intermediate under basic conditions and subsequent Michael addition by water to this intermediate proceeded with high facial selectivity which terminated this total synthesis. Remarkably, the new elansolid derivative2 c shows very good inhibitory effect against Bacillus subtilis and Staphylococcus aureus (including MRSA) similarly to the best elansolid derivatives reported so far. Consequently, the hydroxyl group at C20 is not essential for antibacterial activity. Abstract : Pull the trigger : 20‐Deoxy‐elansolid B1, the proposed PKS product of elansolid, was prepared by a biomimetic intramolecular Diels–Alder (IMDA) cycloaddition. The cascade reaction is triggered by a proton and proceeds via a p ‐quinone methide intermediate followed by IMDA. The new deoxy derivative shows strong antibacterial activity despite the absence of the hydroxyl group at C20.